Student Entrepreneurship Development Model at Universities in West Sumatera, Indonesia - Novita, Mona; Prasetyo, Muhammad Anggung Manumanoso; Bashori, Bashori; Badarussyamsi, Badarussyamsi; Nurlailisna, Novi (JURNAL AL-TANZIM, 2022)
This study aims to determine, understand and analyze the higher education entrepreneurship development model. The model implementation process is carried out in stages, from the strategic plan stage, implementation in higher education units to mobilizing the community to participate in entrepreneurial activities. This study uses a qualitative approach with the type of case study conducted at the Padang State University (UNP) West Sumatra Province, Indonesia. The results show that the development model refers to the System Theory, manifested in the VALUE concept (View, appreciate, lead, understand and evaluate). The key factor as the primary capital for the implementation of the model is the milieu of the Padang community, which is thick with the entrepreneurial spirit in a spiritual, religious frame – Muslimprenur. This study implies that the VALUE concept leadership management process can produce output through Muslimpreneur-based student entrepreneurship development, ultimately increasing the value of innovation and independence for students.